2012
DOI: 10.1590/s1413-78522012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Terapia celular da pseudoartose

Abstract: ObjectiveTo assess the safety and efficiency of cell therapy for pseudarthrosis. Implant of the bone marrow aspirate was compared to mononuclear cells purified extemporaneously using the Sepax® equipment.MethodsSix patients with nonunion of the tibia or femur were treated. Four received a percutaneous infusion of autologous bone marrow aspirated from the iliac crest, and two received autologous bone marrow mononuclear cells separated from the aspirate with the Sepax®. The primary fixation method was unchanged,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
2
Order By: Relevance
“…Nine studies evaluated the use of cBMA in bone healing summarized in Table 4 [ 25 - 33 ]. Eight of nine studies reported on the use of cBMA in either non-union or delayed union.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies evaluated the use of cBMA in bone healing summarized in Table 4 [ 25 - 33 ]. Eight of nine studies reported on the use of cBMA in either non-union or delayed union.…”
Section: Resultsmentioning
confidence: 99%
“…One study found a significantly lower number of progenitor cells in patients who did not achieve union as well as a negative correlation between the time needed to obtain union and the concentration of colony forming units in the graft[ 30 ]. Lastly, one study evaluated the efficacy of cBMA in the treatment of open tibia fractures and found adequate bone consolidation and bone callus formation in all patients[ 25 ]. Variation of cBMA application was seen amongst the studies evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O tratamento invasivo das fraturas aumenta os riscos de perda da vascularização óssea, podendo então gerar também complicações pós-operatórias como a proliferação de infecções no local de fratura. Sendo assim, independente do método utilizado como abordagem, não existe uma alternativa de tratamento apresentando somente benefícios e isenção de riscos [1][2][3]5,13,14 . Neste caso, em breve haverá implantação de outra técnica de osteossíntese, porém, atualmente existem outros tipos de alternativa, como a placa onda.…”
Section: Resultsunclassified
“…Estima-se que aproximadamente 5% de fraturas de ossos longos evoluem para tal, que se associa a sintomas específicos e difícil tratamento clínico [1][2][3][4] . Todavia, constitui um processo grave, capaz de gerar incapacidade em nível severo ou lesão permanente nos pacientes.…”
Section: Introductionunclassified